+0  
 
0
54
1
avatar+243 

The system of equations

\(\frac{xy}{x + y} = 1, \quad \frac{xz}{x + z} = 2, \quad \frac{yz}{y + z} = 3\)

has exactly one solution. What is \(z\) in this solution?

 Apr 12, 2020
 #1
avatar+21004 
+1

xy/(x + y)  =  1   --->   xy  =  x + y   --->   xy - x   =  y   --->   x(y - 1)  =  y   --->   x  =  y/(y - 1)

xz/(x + z)  =  2   --->   x  =  2z/(x - z)

yz/(y + z)  =  3   --->   z  =  3y/(y - 3)

 

Substituting the third equation into the second:  x  =  [ 2(3y/(y - 3)) ] / [ 3y/(y - 3) - 2 ]

--->   x  =  (6y) / (y + 6)  

 

Combining this equation and the first equation:  y/(y - 1)  =  (6y)/(y + 6)

--->   y(y + 6)  =  6y(y - 1)

--->    y2 + 6y  =  6y2 - 6y

--->             0  =  5y2 - 12y

--->             0  =  y(5y - 12)

Either  y = 0  or  y  =  12/5                       

 

If  y = 12/5   --->  x  =  y/(y - 1)   --->   x = 12/7

 

If  x = 12/7  and  y = 12/5  --->   z  =  3y/(y - 3)   --->   z  =  -12

 Apr 13, 2020

33 Online Users

avatar
avatar
avatar